Bimbingan Kelompok Teknik Psikodrama untuk Menurunkan Burnout - Nur Indah Wati; Arifin Nur Budiono; Sitti Ernawati (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2018)
School Fullday a school alternative currentlyinterestedin our society especially for parents busy with work. They think choice school Fullday the very effective fortheir childrens. Researchers do observation in class V SDNU 22 Full Day AL HIKMAH Kesilir Wuluhan indicating that mostof the their students have saturation while the school day, due to start morning until the afternoon they are in school. This study aims to know the decline Burnout (saturation learning) using the guidance of group with engineering psikodramaon the students class V SDNU 22 Full Day AL HIKMAH Kesilir Wuluhan the school year 2017/2018.This researche using action researche guidance and counseling (PTBK), while the procedure is used model cycle. Based on the research, after doing post Treatment on cycle 1mshows that the value of the  ofBurnout on students class V SD NU 22 Full Day Al HIKMAH Kesilir Wuluhan the school year 2017/2018 shows the range of low value and has reached the value of the success indicators between the value of 30-50, so the reserchers enoughto do treatment on the cycle of 1. Thus proven that Burnout(saturation learning) can be derived with guidance group with engineering psikodrama. Keywords: Psikodrama, Burnout, Full Day